Resistance of cruciferous crops to turnip root fly - Per Ruuth (Scientific Agricultural Society of Finland, 1988)
Cruciferous crops have been investigated for resistance to turnip root fly (Delia floralis Fallén) in northern Sweden. Resistance variation has been demonstrated in field trials by observations of wilting symptoms, differences in green mass yield, root damages, surviving plants and number of eggs. Laboratory methods for resistance studies and plant selections in controlled environment are presented, and a method for rearing of flies is described. The definitions of antixenosis, antibiosis and tolerance are discussed, and suggestions for resistance breeding presented.